Quality management practices in the south east Asian airlines' operations function - Subagyo, Toto Hardiyanto (Cranfield University, 2002)
Despite the recent Asian economics crisis (1997-1998), air traffic volumes in Asia- Pacific will continue to grow over the next decade. As the market is becoming more and more attractive, the competition amongst the airlines operating in the region has challenged the Southeast Asian carriers. The demanded quality of product/service by the customer has become a crucial issue. The ability to provide quality products and services is increasingly becoming a key determinant of an airline's business success. The quality of any organisation's products and services is determined by the core business or operational processes that create them. If the chain of processes is made effective and efficient, then the resulting products and services will also be effective and efficient. Airline business activities consist of sales and marketing, engineering and maintenance, flight operations, and ground services. For the purpose of this study the operations function, which consists of aircraft maintenance, flight operations and ground services, becomes a focus, as it is the core activity of operational processes that causes the success or failure of delivering quality products and services to the customer. The study was aimed at developing a model of quality management practices for the operations function of the `developing' airlines of Southeast Asia. It was conducted through extensive literature and field studies, based on the quality management practices of certain airlines in Southeast Asia and Western Europe. The study found that there were twelve critical success factors of quality practices in the operations function, which should be managed differently depending on the airlines' organisational contexts, in order to keep their operational effectiveness and efficiency at the required level. The findings configured a model that provides airlines' executives or managers with guidelines, which they can consult in their decision-making process when conducting quality improvement for their organisation. They may well be used by other airlines as well. The findings from the study also contribute to the knowledge of process quality, and the applicability of the quality concept developed in the social and business disciplines of airlines' operational organisation.